Il rapporto banca-impresa artigiana nella provincia di Catanzaro - Trotta, Anna; Mauro, Marianna (Piccola Impresa / Small Business, 2007)
The changes in the Italian banking system, begun during years nineties and not still concluded, as well as the outcome of the Basel Committee on Banking Supervision’s (Basel 2) regarding the international convergence of the regulations governing the capital adequacy, have reopened the debate on the relationship bank-firms; in a more particular way on the necessity to guarantee to SMEs and to the handicraft firms an adapted financial support in order to assure their development and in many cases their survival. The research is aimed to identify the real situation of the bank-small firms relationship, the level of qualitative and quantitative information that the financial enterprises can transfer to the system, the perspectives of survival and development of the same enterprises, considering the changes in action, linked to the future introduction of the new Basel agreement; it currently proposes numerous changes in the actual rules, above all as regard as the credit risk credit and the associated measure of eligible capital for banks. The study, conducted at the moment, on the handicraft enterprises located in the province of Catanzaro (the seat of Calabria local government), take part in the widest debate to a national level. Analogous researches started in other Italian regions testifies a raising interest from scholars and professionals on such topic, not still inquired in systematic way. To carry on the research the questionnaire methodology is been chosen. A medium length, multi-part questionnaire was designed to identify business characteristiques and their relationship with local banks. It contains both open-ended and close-ended questions. This flexible format was used to solicit the most accurate and complete responses from SME.